1997
DOI: 10.1172/jci119633
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mucosal homing receptor alpha4beta7 by circulating CD4+ cells with memory for intestinal rotavirus.

Abstract: The integrin ␣ 4 ␤ 7 mediates lymphocyte binding to mucosal addressin cell adhesion molecule-1, and its expression defines lymphocytes capable of trafficking through the intestines and the intestinal lymphoid tissues. We examined the ability of discrete ␣ 4 ␤ 7 hi and ␣ 4 ␤ 7 Ϫ subsets of circulating memory phenotype (CD45RA Ϫ ) CD4 ϩ T cells to proliferate in response to rotavirus, a ubiquitous intestinal pathogen. ␣ 4 ␤ 7 hi memory (CD45RA Ϫ ) CD4 ϩ T cells displayed much greater reactivity to rotavirus than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
95
0
6

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 21 publications
11
95
0
6
Order By: Relevance
“…ear injection of CPE evoked late-phase cutaneous responses, as demonstrated by ear thickness with a concomitant influx of eosinophils into the ear tissue. The current understanding is that the initial site of Ag priming, i.e., the draining LNs, where dendritic cells (DCs) carrying Ag first interact with T cells, determines the future homing of memory/effector T cells and, hence, the site at which immune-inflammatory responses will manifest upon Ag re-exposure (23)(24)(25)(26)(27). This notion along with the observations that we made in the lung and skin prompted us to comprehensively seek for evidence of peanut-specific immunity in a variety of LNs.…”
Section: Discussionmentioning
confidence: 99%
“…ear injection of CPE evoked late-phase cutaneous responses, as demonstrated by ear thickness with a concomitant influx of eosinophils into the ear tissue. The current understanding is that the initial site of Ag priming, i.e., the draining LNs, where dendritic cells (DCs) carrying Ag first interact with T cells, determines the future homing of memory/effector T cells and, hence, the site at which immune-inflammatory responses will manifest upon Ag re-exposure (23)(24)(25)(26)(27). This notion along with the observations that we made in the lung and skin prompted us to comprehensively seek for evidence of peanut-specific immunity in a variety of LNs.…”
Section: Discussionmentioning
confidence: 99%
“…The oral mode of delivery has the potential to confer long-term mucosal immunity against pathogens such as HIV-1 if it can induce antigen specific cells to home to the gut as shown in previous studies [25][26][27][28], but efforts to stimulate immunity through this route may inadvertently induce oral tolerance instead [29]. Oral vaccine development using replication defective adenovirus, such as the vector we have tested, may be impeded by vector instability in the acidic environment of the stomach, through which it must pass to ensure antigen presentation and maximum exposure to and uptake by the antigen presenting cells of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…This is, in part, accomplished by the acquisition of differential homing instructions, including, but not limited to, unique adhesion molecules (30 -32) and chemoattractant receptors (25)(26)(27)(28)(29) that direct lymphocytes to tissues in which they are most likely to re-encounter their cognate Ag. Indeed, memory/effector T cells have been identified that selectively home to cutaneous (45)(46)(47) and various mucosal (30,31,33) tissues. Whether this tissue-selective paradigm is also evoked during tolerance induction is unknown.…”
Section: Discussionmentioning
confidence: 99%